ANALYSIS OF THE INFLUENCE OF KNOWLEDGE OF BUSINESS FINANCIAL MANAGEMENT AND FAMILY ENVIRONMENT ON INTEREST IN ENTREPRENEURSHIP (Analytic Study on FEB UMI Students, Makassar) - Yanti, Eka Devi; Laba, Abd Rakhman; Pakki, Erlina (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
This study aims to identify the effect of knowledge of business financial management, and family environment on the interest in entrepreneurship. The population of this study was a S1 student at the Faculty of Economics and Business, University of Muslim Indonesia Makassar, with the sampling technique used was accidental sampling, in 100 semester FEB students as respondents. Quantitative data analysis methods and using several tests such as validity testing, reliability test, classical assumption test, multiple linear regression tests, and the coefficient of determination test (adjusted r square. positive about entrepreneurial interest. By understanding the effects between these variables, it is hoped that this research can provide insight which is useful in supporting the development of entrepreneurial interests and efforts to increase the number of qualified entrepreneurs.